The Effect of Supplementary Feeding (PMT) on the Nutritional Status of Toddlers Aged 2-5 Years - Hidayah, Ilma Salsabilla; Kusumawati, Estri; Pribadi, Eko Teguh; Hadi, Moch. Irfan (International Conference on Sustainable Health Promotion, 2025)
The nutritional status of toddlers plays a crucial role in determining the health quality and human resources of a nation. Although there has been a decline in stunting rates, nutritional challenges remain high, thus requiring appropriate intervention strategies, including supplementary feeding (PMT). Objective: This study aims to examine the effect of supplementary feeding consumption on improving the nutritional status of undernourished toddlers and to measure the success of PMT implementation within community health centers. Methods: This study utilized an analytic quasi-experimental design with a cross-sectional approach. Samples were taken using total sampling technique with a total of 12 samples. Inclusion criteria included toddlers with undernutrition status (weight-for-age and height-for-age between -3 SD and less than -2 SD) who received supplementary feeding. Normality tests showed data were normally distributed; therefore, the parametric Paired T-Test was used for statistical analysis. Result: The study results showed that among toddlers monitored during PMT consumption, one toddler (8.3%) experienced improvement, while the others remained stable with possible weight gain. Conclusion: This study indicates that supplementary feeding (PMT) has a significant effect on improving the nutritional status of undernourished toddlers (P=0.004).